Anti-contactin-associated protein-like 2 antibody-associated encephalitis in children: A case report and literature review - Dou, Qingyang; Li, Renke; Shu, Xiaomei (Frontiers in Pediatrics, 2022)
Background: Anti-Contactin-associated protein-like 2 (CASPR2) antibody-associated encephalitis is a rare group of autoimmune diseases that causes extensive damage to the central and/or peripheral nervous system. Case presentation: Here, we reported a case of anti-CASPR2 antibody-associated encephalitis in a 12-year-old male patient with symptoms of headache, consciousness disturbance, mental abnormalities, urinary incontinence, twitching in the extremity muscles, and involuntary movements. The autoimmune encephalitis-associated antibodies testing showed that CASPR2-associated antibodies were positive, and electroencephalography showed diffuse slow waves. The child's status significantly improved after receiving immunotherapy with intravenous methylprednisolone and immunoglobulin. Conclusions: Anti-CASPR2 antibody-associated encephalitis has been rarely reported in children, with a complex clinical presentation and a low incidence of combined tumors. Most pediatric patients have a favorable prognosis, and relapse is uncommon.